Analysis of The Risk of Work Accidents on Oil Palm Harvesting Employees at Afdeling Golf in PT. Subur Abadi Wana Agung - Sri Ngapiyatun; Rasiani; Wartomo; Humairo Aziza; Arief Rahman (Jurusan Pertanian Politeknik Pertanian Negeri Samarinda Kampus Sei Keledang Jalan Samratulangi, Kotak Pos 192 Samarinda 75123, 2024)
Many accidents in oil palm plantations are caused by risks such as harvesting activities. Even though the K3 system has been implemented, accidents still occur because there is a high potential risk of work accidents, so companies need to manage them so that the level of work accidents can be reduced. Research objectives: identify potential dangers and risks of work accidents for harvest employees, carry out an assessment and analysis of the level of value of the risk of harvesting work activities using the HIRARC method and recommend ways to control the potential risk of work accidents during harvesting based on the K3 risk management hierarchy, namely substitution, elimination, PPE and administration. Activities identified as having potential dangers and risks are sharpening tools, cutting fruit, cutting midribs, transporting fruit to TPH, and arranging fruit in TPH. There are 2 levels of risk assessment, namely low risk low risk (sharpening tools, cutting fruit at risk of being injured by thorns and the risk of material waste being exposed to sore eyes, arranging fruit in TPH), medium risk, medium risk (cutting the fronds at risk of falling fronds, swelling from wasp stings and fever, transporting fruit to TPH), and controlling risks such as substitution, elimination, using PPE, administration and being careful when working and paying attention to land conditions.